Staging the Ghost Story - Jones, Kelly. author. aut Link
VII, 259 p.
Keywords: Staging the Ghost Story is the first book to offer a critical appraisal of the centuries-long relationship between the ghost story and the English stage. The book balances a critical consideration of the ghost story in performance, its history, its cultural politics, and its generic conventions, with practical insight regarding the valency of live representations of the supernatural, the challenges of embodiment, and the power of storytelling. Throughout, it draws upon accompanying interviews with prominent directors, playwrights, performers and stage designers in the industry, including Mark Gatiss, Robin Herford, Michael Holt, Danny Robins, Robert Lloyd Parry, Rebecca Vaughan, Tajinder Singh Hayer, Glen Neath, Adam Z. Robinson, Richard Sutton, Paul Voodini, and Jonathan Goodwin. With a focus upon the seminal elements of theatrical performance: time, space, bodies, devices, and audience, the book invites the elusive shadows of the ghost story to take centre stage. Kelly Jones is senior lecturer in Drama at the University of Lincoln, UK, where she specialises in theatrical realisations of the supernatural and the Gothic. She is the co-editor of Contemporary Gothic Drama: Attraction, Consummation and Consumption on the Modern British Stage (2018).